2018
DOI: 10.1177/1534735418775828
|View full text |Cite
|
Sign up to set email alerts
|

Targeting VEGF/VEGFRs Pathway in the Antiangiogenic Treatment of Human Cancers by Traditional Chinese Medicine

Abstract: Bearing in mind the doctrine of tumor angiogenesis hypothesized by Folkman several decades ago, the fundamental strategy for alleviating numerous cancer indications may be the strengthening application of notable antiangiogenic therapies to inhibit metastasis-related tumor growth. Under physiological conditions, vascular sprouting is a relatively infrequent event unless when specifically stimulated by pathogenic factors that contribute to the accumulation of angiogenic activators such as the vascular endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 190 publications
0
10
0
Order By: Relevance
“…57 However, VEGF alone is not sufficient to promote cell tumorigenicity, suggesting that additional angiogenic factors and cytokines (such as TGF-β, tumor necrosis factor-α [TNF-α], interleukin-6 [IL-6]) regulated in their expression also are critical for an effective tumor initiation. [58][59][60] Additionally, MSC-specific VEGF expression appears to be tightly regulated based on physiological need, and may represent a superior means of inducing therapeutic angiogenesis. 61,62 Therefore, MSCs labeled with iron oxide nanoparticles might be advantageous to repairing damaged tissues.…”
Section: Cytokine Release From Mscs Labeled With Iron Oxide Nanopartimentioning
confidence: 99%
“…57 However, VEGF alone is not sufficient to promote cell tumorigenicity, suggesting that additional angiogenic factors and cytokines (such as TGF-β, tumor necrosis factor-α [TNF-α], interleukin-6 [IL-6]) regulated in their expression also are critical for an effective tumor initiation. [58][59][60] Additionally, MSC-specific VEGF expression appears to be tightly regulated based on physiological need, and may represent a superior means of inducing therapeutic angiogenesis. 61,62 Therefore, MSCs labeled with iron oxide nanoparticles might be advantageous to repairing damaged tissues.…”
Section: Cytokine Release From Mscs Labeled With Iron Oxide Nanopartimentioning
confidence: 99%
“…Therefore, the development of relevant inhibitors has great significance in anti-angiogenesis. Recent years, a number of studies have shown that Traditional Chinese Medicine can regulate VEGF in multi-targets and multi-pathways ( Qin et al, 2018 ; Zhang et al, 2018a ). Studies have found that the proliferation of vascular endothelial cells was significantly inhibited by leech and cantharides through reducing the expression of VEGF and matrix metalloproteinase 9 (MMP-9) ( Yao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies on the anti-angiogenesis activities of monomer and Chinese herbal extracts are very transparent; however, basic research on compounds remains in its infancy. In the theory of TCM, formulae with multiple combinations of herbs are more frequently used for clinical therapy [ 182 ]. The complexity of alternative and complementary medicines makes it extremely difficult to systematically explain molecular mechanisms adequately using routine methodology [ 183 ].…”
Section: Discussionmentioning
confidence: 99%